Isolation and charazterization of pulp from Perlis sugarcane bagasse and rice straw - Suhardy, Daud; Farhana Diyana, Mohd Yunos; Farizul Hafiz, Kasim; Saiful Azhar, Saad; Harbant, Singh (Forest Research Institute of Malaysia (FRIM), 2009)
Organized by Forest Research Institute of Malaysia (FRIM), 16th - 18th August 2005, Hotel Hilton, Kuala Lumpur, Malaysia.